Style radzenia sobie ze stresem a kompetencje społeczne pielęgniarek psychiatrycznych - Maciaszek-Tume, Adrianna; Kotarba, Agnieszka; Borowiak, Ewa (Kultura-Społeczeństwo-Edukacja, 2024)
The aim of the study was to assess the relationship between coping styles with stress and the level of social competence in a group of psychiatric nurses. The research was conducted on a group of 100 psychiatric nurses working in the Lodz Voivodeship. The study used a sociodemographic survey, Social Competence Questionnaire (SCQ), and Coping Inventory for Stressful Situations (CISS).The group of psychiatric nurses obtained the highest average for the task-oriented style and the lowest for the emotional style. The differences between the average coping styles with stress did not reach statistical significance, therefore the dominant coping style with stress cannot be determined. For all three styles, the results in the studied cohort were at an average level. In the examined population, social competences related to effective behavior in social exposure situations were at the highest level, and for effective functioning in intimate situations, they were at the lowest level. The qualitative results of all the studied social competences corresponded to a low level. The analyses did not confirm the existence of a relationship between coping style with occupational stress and social competences.